2021
DOI: 10.1162/jocn_a_01750
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Contribution of Extrastriate Responses to Representational Enhancement of Gaze Targets

Abstract: Before saccadic eye movements, our perception of the saccade targets is enhanced. Changes in the visual representation of saccade targets, which presumably underlie this perceptual benefit, emerge even before the eye begins to move. This perisaccadic enhancement has been shown to involve changes in the response magnitude, selectivity, and reliability of visual neurons. In this study, we quantified multiple aspects of perisaccadic changes in the neural response, including gain, feature tuning, contrast response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Pre-saccadic modulation of firing includes increases in average rate, higher stimulus selectivity, and reductions in variability of response (Moore & Chang 2009; Steinmetz & Moore 2010; Merrikhi et al 2017). Similar enhancements have been identified as well in extra-striate macaque area MT and related to increases in neural sensitivity (Merrikhi et al, 2021). It has also been shown that at off-target locations there are enhancements when the RF stimulus matches features of the saccade target (Burrows et al, 2014).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Pre-saccadic modulation of firing includes increases in average rate, higher stimulus selectivity, and reductions in variability of response (Moore & Chang 2009; Steinmetz & Moore 2010; Merrikhi et al 2017). Similar enhancements have been identified as well in extra-striate macaque area MT and related to increases in neural sensitivity (Merrikhi et al, 2021). It has also been shown that at off-target locations there are enhancements when the RF stimulus matches features of the saccade target (Burrows et al, 2014).…”
Section: Introductionsupporting
confidence: 78%
“…However, these differences could also reflect differences in the behavioral tasks, which would be interesting to explore in future studies. Specifically, while previous paradigms measured variability during extended periods of sustained central fixation (Mitchell et al, 2007; Li & Basso, 2008; Moore & Chang, 2009; Cohen & Maunsell, 2009; Steinmetz & Moore, 2010; Merrikhi et al, 2021) we allowed marmosets to initiate saccades with no delay at stimulus onset. It is known that stimulus onsets can quench noise correlations (Churchland et al, 2010), which could explain the modest reductions in our task where saccades were initiated within 150 to 250ms of stimulus onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found unexpectedly that the time course and response components of the spatial bias matched that of another perisaccadic perceptual phenomenon, namely the enhancement of neural sensitivity around the ST. This representational ST enhancement can link to presaccadic enhanced ST perception reported in psychophysical studies 35,37,50 and to presaccadic increased stimulus selectivity 24,26,51,52 or ST remapping 38,39 evidenced in neurophysiological studies. The shared neural response components underlying the ST representational enhancement and bias suggest that the brain likely trades off and prioritizes saccade target representation with consequential biases in location perception.…”
Section: Introductionmentioning
confidence: 65%
“…A complete synchronization is a state where all the neurons in the network oscillate at the same dynamics simultaneously. Synchronization plays an essential role in the brain's general functioning, including working memory and motor planning [20][21][22][23]. A variety of types of synchronization have also been observed in patients with epileptic seizures [24], Parkinson's disease [25], schizophrenia [26], and other brain disorders.…”
Section: Introductionmentioning
confidence: 99%